Comparative Study of Visual Analogous Scale, Adverse Effect of Antiemetics in Prophylaxis of Post-Operative Nausea and Vomiting in Patient Undergoing Laparoscopic Surgeries - Yogesh Barshiliya; Danish Ahmed; Vikas Kumar (International Journal of Pharma and Bio Sciences, 2020)
Postoperative Nausea and Vomiting (PONV) is common after general anaesthesia. It is a significant cause of morbidity, especially in patients undergoing laparoscopic surgery. The most common and distressing symptoms, which follow anaesthesia and surgery, are pain and emesis. The syndrome of nausea, retching and vomiting is known as “sickness" and each part of it can be distinguished as a separate entity.Nausea is defined as the subjectively unpleasant sensation associated with awareness of the urge to vomit. Retching is defined as the labored, spastic, rhythmic contraction of the respiratory muscles without expulsion of the gastric contents and Vomiting is defined as the forceful expulsion of gastric contents from the mouth. The present research work was carried to compare the visual analogue scaleand adverse effects of widely used antiemetic in prophylaxis of PONV in patients undergoing laparoscopic surgeries under general anaesthesia. This study was carried out after an institutional ethics committee approval and after filling informed consent form by all the patients of ASA I and II (American Society Anaesthesiologists) of either sexes, aged between 20-60 years randomized selected into the three groups. Group A (n=25), Metoclopramide 10 mg as a single dose was given by slow i.v inj. with dilution over 5-10 min, prior to induction. Group B (n=25), Ondansetron 4 mg as a single dose was given by slow i.v inj. with dilution over 5-10 min, prior to induction. Group-C (n=25) inj. Granisetron 3 mg as a single dose was given by slow i.v inj. with dilution over 5-10 min, prior to induction.The results of our studyvisual analogue scale which was used to determine the pain severity was not statistically different in all three groups.There was no major adverse effect observed in 24 hrs post operative period in any of the three groups. The common adverse effects were headache, dizziness & mild constipation. Headache occurred in all the three groups with similar frequency and resemblance to other studies. The granisetron had a low degree of adverse effect except headache.